A Review of Antibacterial Agents in Endodontic Treatment - Rahimi, Saeed; Janani, Maryam; Lotfi, Mehrdad; Shahi, Shahriar; Aghbali, Amirala; Vahid Pakdel, Mahdi; Salem Milani, Amin; Ghasemi, Negin (Iranian Endodontic Journal, 2014)
Microorganisms play a major role in initiation and perpetuation of pulpal and periapical diseases. Therefore, elimination of the microorganisms present in the root canal system is the fundamental objective of endodontic treatment. The use of mechanical debridement, chemical irrigation or other antimicrobial protocols and intra-canal medicaments are critical to attain this goal. The aim of this article was to review the antimicrobial agents and their properties in endodontics.